Hamiltonian Systems of Schrödinger Equations with Vanishing Potentials - Ubilla-Lopez, P (World Scientific, 2022)
In this paper, by means of minimax techniques involving Cerami sequences, we prove the existence of at least one pair of positive solutions for a Hamiltonian system of Schrödinger equations in N with potentials vanishing at infinity and subcritical nonlinearities which are superlinear at the origin and at infinity. We establish new estimates to prove the boundedness of a Cerami sequence. © 2022 World Scientific Publishing Company.